The Civil Service Commission 1855-1991 : a Bureau Biography. (Taylor & Francis, 2004)
The presidency was neither designed nor expected to act in concert with the American people; the framers intended Congress to represent the popular will. Contemporary presidents are elected on the promise of being the direct representative of the people. There is an implicit deal between the president and voters: election to office in return for responsiveness to voter concerns. As The Policy Partnership shows, this relationship has been crumbling for some time. Presidents frequently break campaign promises and make unpopular decisions, while the public rarely bands together to demand attention to policy concerns. Many people simply do not vote; political elites take advantage of this indifference to advance their own agendas.